Analisis Tekno Ekonomi Pembangkit Photovoltaic Pada Skema Load Sharing Di Gedung Pendidikan Sragen - Azzam Reza Ahmad Mujahid; Agus Ulinuha (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
The increasing demand for electricity and high dependence on the utility power grid have driven the adoption of photovoltaic (PV) power generation as an environmentally friendly alternative energy source. This study aims to analyze the techno-economic feasibility of a load-sharing PV power generation system, focusing on technical analysis, operational costs, electricity bill savings, and environmental impacts. The research was conducted using quantitative methods to compare energy from photovoltaic generation and the grid, carbon emission calculations using an emission factor of 0,87 kgCO₂/kWh, and economic evaluation through parameters such as Net Present Value (NPV), Return on Investment (ROI), Cost of Energy (COE), and Payback Period (PP). The research results indicate that the photovoltaic panel generation system enables reducing utility grid energy consumption and reducing carbon emissions by 4,85 tons of CO₂ in 2024, increasing to 8,45 tons of CO₂ in 2025. The economic analysis indicates that the NPV value is not yet optimal; however, the ROI stands at 15%, the COE is Rp. 980.08/kWh, and the Payback Period is 6,56 years. The system is feasible for long-term investment. Overall, the implementation of the photovoltaic power plant demonstrates good potential in supporting carbon emission reduction, increasing the utilization of renewable energy, and reducing dependence on fossil-based energy.